Структурированная вода и ее применение в сельском хозяйстве - Kolesnikova A. D. (Academic community of students, 2016)
This article presents a rationale for the relevance of the use of structured water in the various spheres of agriculture and also describes the process and methods of its receipt.
Keywords: вода; урожайность; сельское хозяйство; молекулы; agriculture; структуризация; ионы; предпосевная обработка; structuring; water; molecules; ions; pre-treatment; the yield